Students' Responses to Receiving Social Support From Peers in FKIP Universitas Lambung Mangkurat - Fariqah, Wanda; Putro, Herry Porda Nugroho; Rochgiyanti, Rochgiyanti; Susanto, Heri; Permatasari, Melly Agustina (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
This study aims to analyze the responses of students who are completing their final assignments in receiving social support from peers. This study is a qualitative study using a descriptive phenomenological approach. The stages used in this study include data collection, data analysis and data validity testing. The results of the study show that students provide two forms of responses, namely (1) closed responses in the form of feelings such as happiness, someone paying attention, sadness, shame, and depression; and (2) open responses in the form of behavioral changes such as being more diligent, more productive, more effective when given social support in the form of direct advice to implement the advice given. These findings indicate that peer social support plays an important role emotionally and behaviorally in accelerating the completion of final assignments.